LAW ENFORCEMENT AGAINST ACTIONS OF TERRORISM AND SEPARATISM OF THE INDEPENDENT PAPUA ORGANIZATION (OPM) IN PAPUA IN MAINTAINING THE SECURITY STABILITY OF THE STATE OF INDONESIA - Iskandar, Iskandar (Program Studi Hukum Tata Negara, 2024)
The Free Papua Organization (OPM) is a separatist organization and terrorist group that has been going on since 1965 and wants the independence of the land of Papua. The OPM's actions have resulted in many civilian casualties, law enforcement officers, and the TNI. OPM crimes must be stopped immediately, and law enforcement must be carried out. This research is normative legal research, using a statutory, conceptual, and historical approach. The primary and secondary legal materials are primary and secondary. Based on the results of the study, it was found that the OPM action had been going on since 1965, which was accompanied by physical attacks; a form of dissatisfaction with the Indonesian government caused the actions of this separatist group. Efforts to prevent OPM's separatist attitude are the government revoking DOM operations, granting special autonomy, and allowing the raising of the morning flag and singing the song